An evidence-informed, community-engaged approach to designing a large-scale, impact-oriented research funding initiative to foster the implementation of transformative integrated care: a multi-methods qualitative study - Nida Shahid; Jessica Nadigel; Rhonda Boateng; Richard H. Glazier; Meghan McMahon (Implementation Science Communications)
Abstract Background Integrated care is a promising strategy to advance system transformation, care coordination, equity, and better health outcomes. Health services and policy research can drive evidence-informed health system improvements but is often underutilized. To optimize the relevance and impact of integrated care research as a transformative lever for better health and system outcomes, the Canadian Institutes of Health Research’s Institute of Health Services and Policy Research (CIHR-IHSPR) designed a large-scale, evidence-informed, community-engaged research funding initiative. This paper outlines the approach and methods used by CIHR-IHSPR and describes how they informed the design and development of Transforming Health with Integrated Care (THINC), a large-scale, impact-oriented research funding initiative that promotes the adoption and proliferation of integrated care in Canada. Methods A multi-method qualitative, community-engaged approach was used to inform the design of a research funding strategy. Key features of the approach included multiple evidence inputs (retrospective and prospective information from primary [key informant interviews, focus groups, and a workshop] and secondary [CIHR funding data and literature review] sources), pan-Canadian reach of community engagement, involvement of diverse interest-holders, iterative data collection and analysis, and a commitment to identifying shared priorities through a community-engaged process. Findings There was consensus across the evidence inputs that implementing, adapting, and scaling evidence-informed integrated care interventions is crucial for real-world impact. Strategies found important for improved research relevance and impact include implementation science, rapid response, embedded research, and knowledge mobilization, along with key initiative design elements such as co-leadership, cross-jurisdictional and interdisciplinary teams, and a focus on the Quintuple Aim. Priority populations were also identified for maximizing the potential benefit and impact of the research. These findings informed the design of THINC, resulting in a multi-program initiative aligned to a shared goal of evidence-informed integrated care transformation. A collaborative design approach fostered shared objectives, commitment from multiple partner organizations, and resources to increase the initiative’s size and scope. Conclusions The study demonstrates the feasibility of using an evidence-informed, community-engaged approach and the influence and benefits of the approach in designing a large-scale research funding initiative that aims to be transformational and impactful.